2021
DOI: 10.1371/journal.pone.0248893
|View full text |Cite
|
Sign up to set email alerts
|

Placing sensors in sewer networks: A system to pinpoint new cases of coronavirus

Abstract: We consider a proposed system that would place sensors in a number of wastewater manholes in a community in order to detect genetic remnants of SARS-Cov-2 found in the excreted stool of infected persons. These sensors would continually monitor the manhole’s wastewater, and whenever virus remnants are detected, transmit an alert signal. In a recent paper, we described two new algorithms, each sequentially opening and testing successive manholes for genetic remnants, each algorithm homing in on a neighborhood wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Nourinejad et al 26 have advocated for the use of in-sewer SARS-CoV-2 network sensors, and our results suggest that such sensors would be best placed across different population levels rather than in street line locations of similar populations. Additionally, Larson et al 27 suggested that a sampling of 5 to 10 community locations might be required to iteratively find a COVID-19 "patient zero".…”
Section: Discussionmentioning
confidence: 62%
“…Nourinejad et al 26 have advocated for the use of in-sewer SARS-CoV-2 network sensors, and our results suggest that such sensors would be best placed across different population levels rather than in street line locations of similar populations. Additionally, Larson et al 27 suggested that a sampling of 5 to 10 community locations might be required to iteratively find a COVID-19 "patient zero".…”
Section: Discussionmentioning
confidence: 62%
“…In a clinical setting, individual contributions to a positive pooled sample can be retested to identify the source(s) of the positive; this is not so for wastewater samples. Although researchers have proposed in-sewer sensor networks that would isolate positive building outflows (12), such networks would require much cheaper and faster instrumentation and methods for detecting SARS-CoV-2 in wastewater. Moreover, the prospect of tracing genetic signals in wastewater back to individual sources amplifies privacy and ethical concerns surrounding WBE (13).…”
Section: Unbiased Testingmentioning
confidence: 99%
“…Overall, this report provides the first empirical evidence for several past simulation studies ( Paltiel & Schwartz, 2021 ) showing that achieving a high vaccination rate is an important policy tool for the administrations of institutions of higher education. While institutions of higher education have benefited from several other policies ( Larson et al, 2020 ; Nourinejad et al, 2021 ) including higher test frequencies ( Paltiel, Zheng, et al, 2020 ; Schultes et al, 2021 ), and it is difficult to separate the effect of the mandates from other policies in correlational studies, our difference-in-differences method controls for the historical trends for each university and isolates Fall 2021 policy changes from other policies that were in place before Fall 2021. Moreover, it is likely that institutions with such high vaccination levels had a lower risk perception, leading to more interactions; thus, our estimation points to a lower bound effect of mandating vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, this report provides the first empirical evidence for several past simulation studies (Paltiel & Schwartz, 2021) showing that achieving a high vaccination rate is an important policy tool for the administrations of institutions of higher education. While institutions of higher education have benefited from several other policies (Larson et al, 2020;Nourinejad et al, 2021) including higher test frequencies Schultes et al, 2021), and it is difficult to separate the effect of the mandates from other policies in correlational studies, our difference-in-differences method controls for the historical trends for each university and isolates…”
Section: Discussionmentioning
confidence: 99%